PENGARUH BERAT NaOH TERHADAP PEMBENTUKAN ZEOLIT DARI ABU DASAR BATUBARA (BOTTOM ASH) - Sunarti Sunarti; Nurul Hidayat Aprilita; Indriana Kartini (Program Studi Pendidikan Kimia FKIP Universitas Pattimura, 2011)
The effect weight of NaOH to zeolite formation from coal bottom ash has been investigated. Zeolite was synthesized by fussion with NaOH at 550oC, and variations weight of NaOH respectly: 2.5; 3.5; 4.5; 6.5 g and weight of Coal bottom ash is 2.5 g. The resulted by fussion with NaOH was hydrothermal treatment at 100oC, and 24 hour. The characterization result with IR Spectrophotometer and X-Ray diffraction showed that at variations weigh of NaOH/bottom ash (r) = 1, Na-P zeolite with increased intensity, A zeoliteand faujasite decreased intensity were obtained. The treatment r= 1.4, faujasite with increased intensity, but Na-P and A zeolite decreased intensity were obtained. The treatment r=1.8, sodalit increased intensity, and faujasite decreased intensity were obtained. The Treatment r=2.6, was obtained.